Indications for the Occurrence of Gas Hydrates in the Fram Strait from Heat Flow and Multichannel Seismic Reflection Data. (9th February 2014) - Geissler, W. H.; Pulm, P. V.; Jokat, W.; Gebhardt, A. C.
Abstract : The distribution of gas hydrates recently raised increased attention, especially along glaciated continental margins, due to its potential importance for slope stability and global climate. We present new heat flow data together with multichannel reflection seismic data from the central Fram Strait in-between Northeast Greenland and Svalbard. This area is only accessible by icebreaking vessels, and, therefore, knowledge about this area is still sparse. The new heat flow data concur with previous measurements in the region. High temperature gradients of >200 mK/m were recorded along the active spreading zone in the Fram Strait, and gradients of 75 mK/m along the western slope of Yermak Plateau. Along the Northeast Greenland slope, the measured gradients reach 54 mK/m at maximum. Seismic data image bottom-simulating reflections proofing that the known gas-hydrate province spreads much further north along the western slope of the Yermak Plateau than previously known. Existing slide scars indicate that there might be a causal relationship between the occurrence of gas hydrates and slope instability in that area. Along the Northeast Greenland continental margin and in the adjacent abyssal plain, strong indications for the occurrence of gas within the sedimentary basins and for its migration along fault zones and chimney-like structures are found.